Logical derivation and integrating legal knowledge bases: basic algorithms - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 1998)
The article deals with two aspects of integrating legal knowledge bases. One aspect is to compare and detect differences of variants of the legal document being prepared or of documents of different countries in the same legal field. Another aspect is to combine fragments of a legal document prepared by different legislators. We formalize and store legal documents as knowledge bases, so our task turns to integrating knowledge bases. In this article we present comparison and combining algorithms based on derivation by model generation.